Virtual Reality Experiments on Emotional Face Recognition Find No Evidence of Mood-Congruent Effects - Zhong, Lan; Wang, Yamin; Kan, Hong; Ding, Jinhong (Frontiers in Psychology, 2020)
Mood-congruent effects have been demonstrated many times, but few studies have managed to replicate the effect with natural moods. Additionally, the ecological validity of mood induction and real-time observation deficiency remain unresolved. Using a newly developed, virtual reality based eye-tracking technique, the present study conducted real-time observations of mood effects on emotional face recognition with simulated “real-life” pleasant and grisly scenes. In two experiments, participants performed an emotional face recognition task in both positive and negative virtual reality scenes. The recognition tests and gaze tracking results failed to support mood-congruent effects, but did show a mood effect independent of a strong emotional face effect. In a third experiment, participants performed a neutral face recognition task in pleasant and grisly scenes that were matched for arousal levels, and the mood effect disappeared. The results also revealed a robust negativity bias in emotional face recognition, which was found to accompany a mood repair effect.